TEACHING VOCABULARY BY USING PLAYDOUGH FOR SPECIAL NEED STUDENTS - Noor Zakiah; Hafizhatu Nadia; Tenny Murtiningsih (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This research aims to develop a playdough game as a medium for learning English Vocabulary. This research used Classroom Action Research with qualitative methods. This research was carried out in a special school in Banjarmasin, South Kalimantan. The purpose of this research is to facilitate the learning process in the classroom for students with special needs. Playdough media can help students remember vocabulary more easily and train fine motor skills in students, and not only that, playdough can also overcome tantrums and increase students’ focus on learning. Therefore, learning by using playdough can make it easier for students to remember vocabulary, increase focus on learning, and can overcome tantrums in students when studying in class.